Upaya pembentukan karakter religius siswa melalui salat duha dan pengajian kitab taysirul kholaq di SMA Abdul Wahid Hasyim Tebuireng jombang - Sekar Ayu Nissa Nur Ikhsani; Aida Arini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study focuses on the formation of students’ religious character through Duha prayer and the study of the Taysirul Kholaq book at SMA Abdul Wahid Hasyim Tebuireng Jombang. The research aims to: (1) describe the religious character of students, (2) analyze the efforts to build religious character through Duha prayer, and (3) examine the efforts to build religious character through the study of the Taysirul Kholaq book. This research employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing, while data validity was ensured through source triangulation. The findings revealed that: (1) the religious character of students at SMA Abdul Wahid Hasyim Tebuireng Jombang can be categorized as good, as reflected in their habits of performing congregational prayers and Duha prayer, as well as demonstrating discipline, responsibility, and politeness in daily life both inside and outside the school environment; (2) efforts to build religious character through Duha prayer are implemented through daily habituation, structured scheduling, teacher supervision and guidance, role modeling, and the cultivation of students’ awareness of worship; and (3) efforts to build religious character through the study of the Taysirul Kholaq book are carried out through scheduled learning activities, the delivery of moral and ethical teachings, lecture and discussion methods, teacher exemplification, and the habituation of moral values in students’ daily lives. These programs contribute positively to strengthening students’ religious character and behavior.